Implementasi Early Warning System (EWS) Banjir Berbasis IoT untuk Monitoring Kondisi Lingkungan dalam Mendukung Mitigasi Bencana - Moh Diki Maulida Rahman; Solekhan Solekhan (CV. ALIM'SPUBLISHING, 2026)
Flooding is one of the most frequent natural disasters occurring in the Kesambi River area, causing both material and non-material losses. The delay in obtaining information related to rising water levels is a major factor contributing to low community preparedness. This study aims to design and implement an Internet of Things (IoT)-based Flood Early Warning System (EWS) capable of real-time monitoring in flood-prone areas of the Kesambi River. The method used includes hardware design utilizing an ultrasonic-based water level sensor, microcontroller, and communication module for data transmission, as well as software design in the form of a mobile-based monitoring application. The system operates by detecting changes in water level and transmitting data to an IoT platform for real-time visualization and early warning notifications to users. The testing results indicate that the system can measure water levels with good accuracy and transmit data reliably. Furthermore, the system is capable of providing rapid early warnings when the water level reaches a predefined threshold. Therefore, the developed system can improve community preparedness in facing potential floods and reduce the resulting impacts.